IMPROVEMENT OF DATABASE PROTECTION SYSTEM FROM UNAUTHORIZED MODIFICATION BASED ON BLOCKCHAIN TECHNOLOGY AND PROOF-OF-WORK CONSENSUS ALGORITHM - SALIIEVA, OLHA; HRYTSAK, ANATOLIY; BILOUS, VITALII; IVANIUK, TARAS (Herald of Khmelnytskyi National University. Technical sciences, 2024)
In today's digital world, there is an active use of databases, and the relevance of protecting them is growing every day. After all, databases can contain a wide range of confidential information (personal, financial, government, commercial, etc.), unauthorized access to which will lead to irreversible negative consequences, including material damage, reputational losses, and even legal problems. In addition, the number and complexity of cyberattacks is growing every day. Attackers use various methods to gain unauthorized access to databases, such as the use of software vulnerabilities, social engineering methods, brute force attacks, etc. Therefore, the problem of increasing the security of databases against unauthorized modification is of great importance. In this regard, this paper proposes to address this issue by using blockchain technology in combination with the Proof-Of-Work consensus algorithm, which ensures the security and integrity of the system, and helps prevent fraud and abuse by using cryptographic methods to protect the blockchain from unauthorized access and modification. It is also worth noting that the Proof-of-Work algorithm has a number of other advantages, such as decentralization, transparency, and data immutability after it is added. Thus, to achieve the goal, the subject area was analyzed, the known methods on which the operation of database security systems is based were investigated, the architecture and algorithm of the security module were created, which allows for decentralized data storage and, accordingly, increases the level of their security by using a special consensus protocol to coordinate the contents of the registry, as well as cryptographic hashing algorithms and electronic digital signatures to ensure the integrity of the parameter transfer transaction.
Keywords: database; blockchain technology; consensus algorithm; Proof-of-work; cryptographic hashing algorithm; digital signature